One-pot synthesis of Ag-TiO2/reduced graphene oxide nanocomposite for high performance of adsorption and photocatalysis. Issue 7 (May 2017) - Zhang, Lixin; Ni, Changhui; Jiu, Hongfang; Xie, Chunmei; Yan, Jibing; Qi, Guisheng
Abstract: The Ag-TiO2 /r-GO nanocomposite was synthesized via a facile one-pot solvothermal method. X-ray diffraction (XRD), Transmission electron microscopy (TEM), High resolution transmission electron microscopy(HRTEM), UV–vis diffuse reflectance spectroscopy (DRS), Fourier transformed infrared spectroscopy (FT-IR), Photoluminescence (PL) and N2 adsorption-desorption were used for the characterization of prepared samples. The adsorbent and photocatalytic performance of prepared samples were evaluated by remove of Rh B dyes and reduction of CO2 . Both the adsorbent and photocatalytic ability of all the Ag-TiO2 /r-GO samples were much higher than pure hollow TiO2 . The excellent adsorbent capacity can be attributed to the large BET surface area and the enhanced photocatalytic activity can be assigned to the predominant properties of graphene and the localized surface plasmon(LSPR) effect of Ag nanoparticles.